A Comparison of Four Approaches to Evaluate the Sit-to-Stand Movement - Shukla, Brajesh K.; Jain, Hiteshi; Vijay, Vivek; Yadav, Sandeep K.; Mathur, Arvind; Hewson, David J. (IEEE transactions on neural systems and rehabilitation engineering, 2020)
The sit-to-stand test (STS) is a simple test of function in older people that can identify people at risk of falls. The aim of this study was to develop two novel methods of evaluating performance in the STS using a low-cost RGB camera and another an instrumented chair containing load cells in the seat of the chair to detect center of pressure movements and ground reaction forces. The two systems were compared to a Kinect and a force plate. Twenty-one younger subjects were tested when performing two 5STS movements at self-selected slow and normal speeds while 16 older fallers were tested when performing one 5STS at a self-selected pace. All methods had acceptable limits of agreement with an expert for total STS time for younger subjects and older fallers, with smaller errors observed for the chair (-0.18 ± 0.17 s) and force plate (-0.19 ± 0.79 s) than for the RGB camera (-0.30 ± 0.51 s) and the Kinect (-0.38 ± 0.50 s) for older fallers. The chair had the smallest limits of agreement compared to the expert for both younger and older participants. The new device was also able to estimate movement velocity, which could be used to estimate muscle power during the STS movement. Subsequent studies will test the device against opto-electronic systems, incorporate additional sensors, and then develop predictive equations for measures of physical function.